Measuring portfolio salience using the Bradley–Terry model: An illustration with data from Brazil. (February 2019) - Zucco, Cesar; Batista, Mariana; Power, Timothy J.
How do political actors value different portfolios? We propose a new approach to measuring portfolio salience by analysing paired comparisons using the Bradley–Terry model. Paired-comparison data are easy to collect using surveys that are user-friendly, rapid, and inexpensive. We implement the approach with serving legislators in Brazil, a particularly difficult case to assess portfolio salience due to the large number of cabinet positions. Our estimates of portfolio values are robust to variations in implementation of the method. Legislators and academics have broadly similar views of the relative worth of cabinet posts. Respondent valuations of portfolios deviate considerably from what would be predicted by objective measures such as budget, policy influence, and opportunities for patronage. Substantively, we show that portfolio salience varies greatly and affects the calculation of formateur advantage and coalescence/proportionality rule measures.